Evolution From Past to Future Conditions of Fast Ice Coverage in James Bay - Taha, Wael; Bonneau-Lefebvre, Maryse; Cueto Bergner, Arian; Tremblay, Alain (Frontiers in Earth Science, 2019)
Fast ice is often used by coastal communities in the James Bay area for transportation in winter using snowmobiles. Therefore, the extent of fast ice along the James Bay coastline is important for land use and any changes to these extents may have significant impacts on the lifestyles of local communities. The eastern coastline has experienced changes in recent decades that might have affected the ice processes, namely hydrologic modifications due to hydroelectric development by Hydro-Québec along with climatic changes that have been observed worldwide. A statistical analysis in the form of summarized ice charts of the ice extents in the middle of winter have been compiled for the past four decades to highlight any recent changes in ice coverage using data from satellite imagery and ice charts produced by the Canadian Ice Service. A statistical analysis has also been carried out on the freeze-up and breakup dates using historical data. Moreover, a statistical analysis of hydrological data and climatic data has been carried out to determine the long-term and short-term trends in the parameters influencing the ice processes. After testing sensitivity of the past ice regime to climatic and hydrological parameters, the trends detected in the extents of fast ice, as well as freeze-up and breakup conditions, have been correlated with climatic parameters. Using the dominant parameters, a simplified model of the extents of fast ice has been developed, as well as criteria to determine freeze-up and breakup dates. Air temperature projections have also been obtained for two greenhouse gas emissions scenarios using global climate model results to establish future climatic conditions. Finally, projections of the fast ice regime around the year 2050 have been developed to determine a long-term trend covering both historical changes and future conditions. We expect around the year 2050 a recession of the landfast ice coverage of several kilometers, a delay of one to three weeks of the freeze-up dates and an advance of two to ten days of the breakup dates in comparison to the period of 1998-2016 in the James Bay area.